Zastosowanie Metody Trefftza oraz Metody Perturbacji do Zagadnień Przepływów Laminarnych i Turbulentnych w Kanale o Złożonym Przekroju - B. Krajewski (Engineering Transactions, 1970)
In this paper the calculations procedure is presented, allowing to determine the fields of velocities and the field of temperatures in a recti-axial canal having a composite cross-section, with the assumption of turbulent flow. To describe the problem there was utilized and existing mathematical model. The mathematical model mentioned enables to determine the distribution of turbulent viscosity in the cross-section under consideration. Application of the integral transformations allowed to achieve particular solutions, which have been subsequently utilized for the proper solution, using accordingly the Trefftz method and the perturbation method.